What’s in a name? New light shed on Moulin’s Manor, the earliest layout of Elswout in Overveen (Bulletin KNOB, 2012)
Elswout Manor in the village of Overveen near Haarlem, is of great art-historical importance, particularly to the history of Dutch country estates and garden architecture. Although it was not until 1660, during its second period of habitation, that Elswout became renowned for its history as well as its striking Dutch classicist architecture, attributed to Jacob van Campen, the manor dates from 1633-1635.This article deals with the overlooked first period (1633-1654) of Moulin’s Manor, as it was known then, and with the founder Carl du Moulin (1586/1588 to approximately 1667), a wealthy tradesman from Amsterdam, who had formerly lived in Russia, of whom nothing substantial was known except a rumour and the fact that he went bankrupt in 1654. At that time it was assumed that Du Moulin left his manor in an unfinished condition, only to be completed by the next owner, Gabriel Marselis, Commissioner of the King of Denmark. Archival evidence has now shown that Carl du Moulin was patron of the painter-architect Pieter Post, who was already supporting him financially in the spring of 1638. Consequently, it is very likely that Post at least played a part in the design of the original plan, probably as an assistant to Jacob van Campen. The land surveyor and mathematician Pieter Wils may also have been involved in the design and layout of the house and garden.Apart from presenting new facts about the first owner of Moulin’s Manor, the presumable original appearance is reconstructed and reviewed on the basis of an estate map (1642), 17th century paintings, a travellers’ account (1663) and architectural drawings (1805). The rigid cross-symmetrical layout of Moulin’s Manor, showing similarities to Scamozzi’s published design of Villa Molin, may have symbolized the family name.